Revisiting the impact of social performance on financial performance from a global perspective - Hajer Tebini; Pascal Lang; Bouchra MacZali; Blanca Perez-Gladish (International Journal of Business Science & Applied Management (IJBSAM), 2014)
There is a continuing debate in the Corporate Social Responsibility literature as to whether and how firms' social performance (SP) affects their financial performance (FP). Theoretical arguments as well as empirical measurements point to somewhat contradictory results. Most of the empirical work is predicated on rigid conventional models, expressing constant or strictly monotonic marginal returns in the assumed SP-FP relationship. This paper revisits this relationship from a global perspective, relaxing the range of admissible models. A non-monotonic framework incorporating contextual factors is proposed. Five models are tested over a common 17 years horizon. They yield consistent significant estimates and concur on the existence of such a relationship although the latter has evolved over time. They support the notion of a complex SP-FP impact.
Keywords: 650; social performance; financial performance; contingency factors; industrial context; strategy; valuation